Ru(II)‐based antineoplastic: A "wingtip" N‐heterocyclic carbene facilitates access to a new class of organometallics that are cytotoxic to common cancer cell lines. (7th December 2018) - Mondal, Ambarish; Tripathy, Rajat K.; Dutta, Parul; Santra, Manas Kumar; Isab, Anvarhusein A.; Bielawski, Christopher W.; Kisan, Hemanta K.; Chandra, Swapan K.; Dinda, Joydev
Abstract : The syntheses, structures, and chemotherapeutic activities of Ag(I)‐, Au(I)‐, and Ru(II)‐complexes ligated to a novel N‐heterocyclic carbene ligand, 2‐(4‐nitrophenyl)imidazo[1, 5‐a]pyridin‐2‐ylidene (1 ), are described. The corresponding complexes, [Ag(1 )2 ][PF6 ], [Au(1 )2 ][PF6 ] (3 ), and [Ru(1 )( p ‐cymene)Cl][PF6 ] (4 ), were prepared using convenient transmetallation chemistry and characterized using a range of spectroscopic and analytical techniques. X‐ray crystallography revealed that complexes2 and3 adopted linear structures whereas4 exhibited a prototypical "piano‐stool"‐like geometry; the structural assignments were further supported by DFT calculations. A series of in vitro studies revealed that while the aforementioned Ag(I), Au(I) and Ru(II) complexes exhibited significant cytotoxicities against the human colon adenocarcinoma (HCT 116), lung cancer (A549), and breast cancer (MCF7) cell lines, the Ru derivative was most prominent. Abstract : Chemotherapeutic activities of Ag(I)‐, Au(I)‐, and Ru(II)‐complexes of 2‐(4‐nitrophenyl)imidazo[1, 5‐a]pyridin‐2‐ylidene scheduled on human colon adenocarcinoma (HCT 116), lung cancer (A549), and breast cancer (MCF7) cells are described.